Benchmarking sustainability performance: the next step in building sustainable business models. Issue 3 (1st April 2016) - Maltz, Elliot; Bi, Henry H.; Bateman, Mark
Abstract : Developing sustainable business models incorporating effects on people, profit, and planet is becoming an increasingly important strategic issue. Benchmarking with peer companies can assist a company in setting goals of improving its performance. As such, developing a methodology for effectively benchmarking sustainable business practices is an important step in the evolution of sustainability management. However, a company's sustainability performance is composed of many elements that may involve difficult tradeoffs, and its performance may vary over time. In this paper, we propose a data‐driven approach of innovatively adapting statistical process control charts, conventionally used in quality control, to simultaneously compare multiple performance measures and analyze variation in both trend and performance among companies in a given industry. We apply this approach to benchmarking the sustainability performance of companies in the US utility industry and demonstrate it is robust and reliable for benchmarking the performance of companies in virtually all industries. Copyright © 2016 John Wiley & Sons, Ltd.